Import Price Formation and Pricing to Market: A Test on Norwegian Data - Bjørn E. Naug; Ragnar Nymoen (Statistics Norway, Research Department, 1995)
This paper investigates the determinants of Norwegian import prices of manufactures over the period 1970(1) - 1991(4). Multivariate cointegration analysis establishes a long-run relationship between import prices, foreign prices, the exchange rate and domestic unit labour costs. Normalized on import prices, the long-run elasticities are 0.63 (foreign prices and the exchange rate) and 0.37 (domestic costs). Deviations from this relationship are highly significant in a structural import price equation, which also contains positive effects of growth in domestic demand and inflation, as well as a negative effect from the Norwegian unemployment rate. The estimated parameters appear reasonably stable within the sample.
Keywords: C32; C51; C52; C22; D40; F41; L16; 330; Import price formation; pricing to market; domestic effects; Johansen procedure; structural error correction model; super exogeneity.